Résumés as selection tool - Sigríður Dröfn Ámundadóttir 1972- (2013)
The first introduction of applicants, when applying for open positions, is usually through resumes. The need for applicants possessing a wide range of skills and abilities to meet requirements for fast growing international corporations will most certainly increase. Selection and staffing is one of the most important processes in human resources and can be used as a source of sustained competitive advantage. It is therefore vital for organizations to emphasize on improving recruiting and selection practices which will result in better organizational outcomes. With more effective practices the more likely organizations are in hiring and retaining satisfied employees. Applicants provide information pertaining to their KSOA‟s (knowledge, skills and other abilities), education and prior work experience in their resumes that recruiters measure and evaluate. This provides recruiters/HR managers with a cost effective and convenient assessment tool that increases the likelihood of hiring individuals who possess the right abilities and skills to be successful at their jobs. The Cranet (2013) research in Iceland shows that the most used hiring practice for managers is the screening of resume/application form, recommendation and a panel interview (Einarsdóttir., Bjarnadóttir., Ólafsdóttir., and Georgsdóttir, 2012). Based on the value of resumes in the selection process and its shortcomings the researcher wondered if there was a link between the content of resumes and the outcomes of personality assessments. In this explorative study it was investigated whether the presence of information in resumes was related to applicants‟ (N=100) personality assessment (OPQ32). Both practical and significant correlations were found such as personality traits of those who have work experience in supervising others, differences in those who have attained master‟s degree compared to those who do not have a master‟s degree. And finally differences in personality traits with those who reported extracurricular activities like being part of ...